Penerapan Sistem Pendukung Keputusan dalam Penerimaan Pengajar Desain Grafis Menerapkan Metode Preference Selection Index (PSI) - Ben Rahman; Irene Hasian; Nofri Yudi Arifin; Jeperson Hutahaean; Rachmad Andri Atmoko (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
Graphic design teacher is one of the teachers who is really needed in various schools or universities, because graphic design is really needed to provide knowledge that can be used to get jobs according to abilities. However, in accepting graphic design instructors, they must really master the field of design and have a lot of experience in teaching that field. In this research, several criteria are needed including Education, Experience, Creative, Innovative, and Communicative. So with that the criterion data can support this research in solving problems and getting accurate and detailed results. And this research really needs a supporting system to solve this research. The system is a Decision Support System (DSS) and the method used to produce an appropriate ranking, this method is the Preference Selection Index (PSI). So the application of this method can produce the highest rank that will be accepted as a graphic design teacher on behalf of Putra Andiyono with a total score of 1.0331.